IMPLEMENTASI SISTEM INFORMASI DESA BERBASIS SMART VILLAGE DALAM MENDUKUNG TRANSFORMASI DIGITAL DI PEDESAAN STUDI KASUS: DESA SUKADAMAI - Wardhani, Muhammad; Hidayatunnisa'i; Mawansyah, Julfikar (Universitas Palangka Raya, 2025)
Sukadamai Village is located in Manggelewa Sub-district, Dompu Regency, West Nusa Tenggara Province. Sukadamai Village is a remote area situated far from the city center, making administrative services an essential aspect for the community. However, several issues are associated with the management of population data, particularly in administrative processes. The data management is entirely conducted manually, utilizing physical record books and printed office media. Moreover, villagers must visit the village office in person to request information and complete administrative tasks. To address these challenges, the authors developed a web-based village information system that supports the concept of a smart village. This system aims to assist the local government and surrounding community in streamlining administrative tasks and ensuring consistent information dissemination. Based on testing, the system received an 89% approval index, with 30 respondents stating they